Tax Incentives for Supporting Competitiveness of Telecommunication Manufacturers - Irina Dezhina; Tamam Nafikova; Timur Gareev; Alexey Ponomarev (Foresight and STI Governance)
The article is dedicated to the analysis of cost factors, primarily tax burden, that can explain the observable price difference on Russian market between domestic telecommunication equipment and imports from China and USA. The relevance of the research is justified by critical significance of this market for economic, information and technological security of Russian Federation in a changed geopolitical environment. The present methods of tax burden calculation analyzed in the article reveal the subindustry level measurement to be the least studied. Based on data on 42 companies for 2015-2017, the cost structure of telecommunication equipment manufacturing industry is studied, a model for computing the tax burden rate on domestic enterprises using imported components is built. The model is adjusted for cross-country comparison to reflect the specifics of countries’ tax systems. The calculations are based on the assumption of equal production costs in the three countries under examination.A comparative analysis has shown that the tax burden in Russia is on average higher than in USA (almost 3 percentage points) and in China for enterprises operating in preferential economic zones (about 2 percentage points). However, this difference in tax burden rate does not explain the observed price discrepancy on the domestic market (up to 21 percent). Cost of components and cost of debt are additionally examined as the factors elucidating divergence of economic conditions. An approximate assessment of their influence has shown that the effect of reducing average costs with an increase in output of components, which is especially characteristic of China, has the largest impact. For American importers the tax burden level and high-end offer are the main competitive advantages. A number of tariff regulation measures allowing to compensate for the price discrepancy on the domestic market are proposed for innovation policy to stimulate the technological development of national producers.